2001
DOI: 10.1007/s00453-001-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Search and One-Way Trading Online Algorithms

Abstract: Abstract. This paper is concerned with the time series search and one-way trading problems. In the (time series) search problem a player is searching for the maximum (or minimum) price in a sequence that unfolds sequentially, one price at a time. Once during this game the player can decide to accept the current price p in which case the game ends and the player's payoff is p. In the one-way trading problem a trader is given the task of trading dollars to yen. Each day, a new exchange rate is announced and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
271
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(273 citation statements)
references
References 25 publications
(30 reference statements)
2
271
0
Order By: Relevance
“…After introducing the one-way trading problem, El-Yaniv et al gave in [10] an algorithm for the problem that works under the assumption that there are a lower bound m and an upper bound M on the market prices such that p i ∈ [m, M ] for all p i , and that these bounds m and M are known to the algorithm. They proved that their algorithm has competitive ratio O(log(M/m)), and showed that it is optimal by deriving a matching lower bound.…”
Section: Previous Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After introducing the one-way trading problem, El-Yaniv et al gave in [10] an algorithm for the problem that works under the assumption that there are a lower bound m and an upper bound M on the market prices such that p i ∈ [m, M ] for all p i , and that these bounds m and M are known to the algorithm. They proved that their algorithm has competitive ratio O(log(M/m)), and showed that it is optimal by deriving a matching lower bound.…”
Section: Previous Resultsmentioning
confidence: 99%
“…They showed that if there are n buyers, their algorithm has competitive ratio nαβ−(n−1)(α+β)+(n−2) αβ−1 . In [10], El-Yaniv et al also studied another problem similar to the one-way trading problem, namely the 1-max-search problem, in which there is a sequence of prices coming online, and when a price arrives, we have to decide immediately whether we accept the price or not. The objective is to accept the highest price.…”
Section: Previous Resultsmentioning
confidence: 99%
See 3 more Smart Citations